Upaya Meningkatkan Nilai-Nilai Religius Anak Melalui Pendampingan Pembelajaran Al-Qur’an di Dusun Krajan Desa Karangpatihan Kecamatan Pulung Kabupaten Ponorogo - Susi Susanti; Ibnu Muchlis (Social Science Academic, 2023)
This article is about mentoring Al-Qur'an learning as a form of effort to increase children's religious values. That learning of the Koran is very important, especially for children in terms of growing a sense of love for the Koran so that when they grow up they are able to apply the values contained in the Koran in everyday life. Al-Qur'an learning in the Krajan hamlet environment, Karangpatihan village is said to be very lacking due to the existence of ordinary parents who do not understand the Qur'an, the lack of educators to teach Al-Qur'an learning, and the lack of a place that is adequate for Al-Qur'an learning the qur'an. The method used in this activity is the ABCD (Asset Based Community-driven Development) method through various stages, namely the stages of inculturation (introduction to the community), discovery (digging up information in the environment), design (knowing assets or potential and identifying opportunities that exists to be developed), define (supports the implementation of a work program), reflection (reflection or feedback from a work program). This activity received positive support and attention from the local community. The result of this activity is that many children are passionate and enthusiastic about learning the Koran, increasing their knowledge and knowledge about the Koran for children.